PENYULUHAN HUKUM PENDIDIKAN ANTI KORUPSI MASYARAKAT DESA BANGET KECAMATAN KWADUNGAN KABUPATEN NGAWI - Meirza Aulia Chairani; Angga Pramodya Pradhana; Bambang Sukarjono; Retno Iswati (JURNAL DAYA-MAS, 2023)
The purpose of this research is so that the people of Banget Village, Ngawi Regency really understand what is meant by criminal acts of corruption and corrupt behavior and the regulations for eradicating criminal acts of corruption. The history of criminal acts of corruption that have existed since the days of the kingdom, and colonization until now has not changed or not in the least. Year after year there has been no decrease in criminal acts of corruption, in fact, it has become more commonplace in society. Corruption is an extraordinary crime that results in state losses. Unethical behavior is an act that has no indication of crime but is the seed of someone who commits an act of corruption. For this reason, we conducted research on how far the public knows the types of corruption and corrupt behavior. Criminal sanctions for perpetrators of corruption are not low, but even though there have been severe sanctions, there are still many perpetrators of corruption. Corrupt behavior not all people know about the form of this corrupt behavior, the act that triggers the criminal act of corruption. So it is very necessary for the village of Banget, Ngawi Regency, to carry out prevention through anti-corruption education.